Impact of medical treatment on long-term results after surgical ablation of atrial fibrillation in cardiac surgical patients - Feyrer, Richard; Ballazhi, Fatos; Seitz, Timo; Weyand, Michael; Harig, Frank (Annals of Thoracic and Cardiovascular Surgery, 2014)
The aim of this study was to evaluate the long-term outcome (4 years) of high-intensity-focused-ultrasound (HIFU) cardiac ablation, the significance of postablation antiarrhythmic drugs (AADs) and predictors of successful sinus rhythm (SR) restoration.103 patients were prospectively enrolled in a single-center study. The preoperative atrial fibrillation (AF) type was paroxysmal in 36%, permanent in 53%, persistent in 5% and flutter in 6% patients. The left atrial diameter was <50 mm in 78 patients and >50 mm in 25. Long-term results, up to 4 years, and postablation antiarrhythmics were evaluated. Follow-up studies including 12-lead electrocardiogram (ECG) and 24-h Holter ECG obtained at 3 and 6 months in our institute, and 12, 24, and 48 months during outpatient visits.No device- or procedure-related complications or deaths were observed. A pacemaker was implanted in 5% patients. Freedom from AF and flutter at 6-/12-/and 48-month visit were 66%/63%/68% for the entire population, 84%/77%/90% in patients with paroxysmal AF, 50%/46%/40% in patients with permanent AF and at any time in all 6 patients with flutter. No significant changes were noted at 2 years.Postablation results were not statistically different in patients on or not on antiarrhythmic therapy. At discharge, 53% of patients on antiarrhythmics and 55%, not on AADs were free of AF. At the 6-month visit, 66% of patients on AADs versus 69% of patients, not on AADs presented with SR, an improved outcome by 13 percentage points with AADs versus 14 percentage points without AADs (p = 0.65). Patients taking a ?-blocker showed better results in restoration/maintenance of SR after 6 months. No significant difference was noted regarding the use of UltraWand.Sixty-seven percent with a left atrium (LA) diameter <50 mm were successfully converted into SR, vs. 48% with an LA diameter >50 mm. Best results were achieved in patients with paroxysmal AF and LA <50 mm with 81% freedom of AF.AF treatment with HIFU ablation during concomitant cardiac surgery is a safe and effective procedure for restoring SR, especially in patients with AF and especially in patients with a smaller left atrial diameter. No significant difference was noted between the antiarrhythmic and non drug groups regarding restoration and maintaining SR; however, better results were achieved by those taking a ?-blocker.
EVALuna2:16084